A Biodegradable Multifunctional Graphene Oxide Platform for Targeted Cancer Therapy. (1st August 2019) - Martín, Cristina; Ruiz, Amalia; Keshavan, Sandeep; Reina, Giacomo; Murera, Diane; Nishina, Yuta; Fadeel, Bengt; Bianco, Alberto
Abstract: The design of multifunctional materials able to both selectively deliver a drug into cells in a targeted manner and display an enhanced propensity for biodegradation is an important goal. Here, graphene oxide (GO) is functionalized with the chemotactic peptide N ‐formyl‐methionyl‐leucyl‐phenylalanine (fMLP) known to interact with the formyl peptide receptor, which is expressed in different cancer cells, including cervical carcinoma cells. This study highlights the ability of GOfMLP for targeted drug delivery and cancer cell killing and the subsequent degradation capacity of the hybrid. Biodegradation is assessed via Raman spectroscopy and transmission electron microscopy. The results show that GOfMLP is susceptible to faster myeloperoxidase‐mediated degradation. The hybrid material, but not GO, is capable of inducing neutrophil degranulation with subsequent degradation, being the first study showing inducible neutrophil degradation by the nanomaterial itself with no prior activation of the cells. In addition, confocal imaging and flow cytometry using HeLa cells demonstrate that GOfMLP is able to deliver the chemotherapeutic agent doxorubicin faster into cells, inducing higher levels of apoptosis, when compared to nonfunctionalized GO. The results reveal that GOfMLP is a promising carrier able to efficiently deliver anticancer drugs, being endowed with the ability to induce its own biodegradation. Abstract : The design of a multifunctional platform based on graphene oxide is reported. The graphene material is modified with a formyl‐peptide able to enhance the biodegradability of the conjugate, mediated by neutrophil secreted myeloperoxidase, and to target cancer cells. The system delivers the chemotherapeutic agent doxorubicin into cells, leading to apoptosis.